Chirality-influenced antibacterial activity of methylthiazole- and thiadiazole-based supramolecular biocompatible hydrogels. (15th March 2022) - Baddi, Sravan; Dang-i, Auphedeous Y.; Huang, Tingting; Xing, Chao; Lin, Shuangjun; Feng, Chuan-Liang
Abstract: Chiral stereochemistry is a unique and fundamental strategy that determines the interaction of bacteria cells with chiral biomolecules and stereochemical surfaces. The interaction between bacteria and material surface (molecular chirality or supramolecular chirality) plays a significant role in modulating antibacterial performance. Herein, we developed inherent chiral antibacterial hydrogels by modifying the carboxyl groups of our previously reported supramolecular gelator (LPF-left handed phenylalanine gelator and DPF- right handed phenylalanine gelator) with 2-amino-5-methylthiazole (MTZ) and 5-amino-1, 3, 4-thiadiazole-2- thiol (TDZ). The new L/D-gelator molecules initiate self-assembly to form hydrogels through non-covalent interactions (Hydrogen bonding and π-π interactions) verified by FTIR and CD spectroscopy. Morphological studies of the xerogels revealed left and right-handed chiral nanofibers for the gelators' L-form and D-form, respectively. The resulting hydrogels exhibited inherent antibacterial activity against Gram-positive ( Bacillus subtilis, Staphylococcus aureus ) and Gram-negative ( Pseudomonas aeruginosa ) bacteria, with TDZ hydrogels showing more significant antibacterial activity than MTZ hydrogels. Interestingly, the D-form (having right-handed nanofibers) of both hydrogels (MTZ and TDZ) exhibited higher antibacterial activities compared with the left-handed nanofibrous hydrogels (L-form) attributed to the stereoselective interaction of the chiral helical nanofiber. Moreover, the amplification of chirality moving from a molecular to a supramolecular level essentially improved the antibacterial action. Our results provide deep insight into the development of unique supramolecular chiral antimicrobial agents and hint at the potentiality of right-handed nanofibers (D-form) having enhanced antibacterial activity. Statement of significance: Chiral stereochemistry plays a significant role in many biological processes, which determines the interaction of bacteria cells with chiral biomolecules. The interaction between bacteria and material surface (molecular chirality or supramolecular chirality) plays a significant role in modulating antibacterial performance. Here, we deigned and synthesized unique inherent biocompatible supramolecular chiral hydrogel. From this study we concluded that the D-form (having right-handed nanofibers) of hydrogels exhibited higher antibacterial activities compared with the left-handed nanofibrous hydrogels (L-form) attributed to the stereoselective interaction of the chiral helical nanofiber. Additionally, this study also explored the amplification of chirality moving from a molecular to a supramolecular level essentially improved the antibacterial action. Graphical abstract: Image, graphical abstract